Gender Diversity and Securities Fraud - Cumming, Douglas; Leung, T. Y.; Rui, Oliver (Academy of Management Journal, 2015)
We formulate theory on the effect of board of director gender diversity on the broad spectrum of securities fraud, and generate three key insights. First, based on ethicality, risk aversion, and diversity, we hypothesize that gender diversity on boards can operate as a significant moderator for the frequency of fraud. Second, we advance that the stock market response to fraud from a more gender-diverse board is significantly less pronounced. Third, we posit that women are more effective in male-dominated industries in reducing both the frequency and severity of fraud. Results of our novel empirical tests, based on data from a large sample of Chinese firms that committed securities fraud, are largely consistent with each of these hypotheses.